1992
DOI: 10.1111/j.1476-5381.1992.tb14431.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of 5‐hydroxytryptamine and 5‐HT1A receptor ligands on rat dorso‐lateral septal neurones in vitro

Abstract: 1 The actions of 5-hydroxytryptamine (5-HT) and some 5-HTA receptor ligands on neurones in the rat dorso-lateral septal nucleus were recorded in vitro by intracellular recording techniques.2 In the presence of tetrodotoxin (1 tiM) to block any indirect effects, bath application of 30 AM) hyperpolarized the neurones in a concentration-dependent manner and reduced membrane resistance. The hyperpolarization did not exhibit desensitization and was sometimes followed by a small depolarization. 6 The 5-HT2/5-HTlc re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(3 citation statements)
references
References 34 publications
(45 reference statements)
1
2
0
Order By: Relevance
“…In the present study, systemic and local administration of 5‐HT 1A receptor agonist 8‐OH‐DPAT inhibited the firing rate of all the PV‐positive neurons examined in the MS‐DB of sham‐operated rats during hippocampal theta rhythm, and these effects were reversed by the selective 5‐HT 1A receptor antagonist WAY‐100635, indicating that these are 5‐HT 1A receptor‐mediated effects. The present results are supported by the fact that the in vitro recordings of septal neurons in brain slices have revealed that activation of 5‐HT 1A receptors hyperpolarizes the neurons and reduces GABA release from GABAergic neurons (Van den Hooff and Galvan, ; Fink and Gothert, ), and consistent with the well‐established role of 5‐HT 1A receptors in the control of neuronal firing of other brain areas. Therefore, the decreased firing rate of PV‐positive neurons in the MS‐DB induced by systemic administration of 8‐OH‐DPAT most likely reflects the direct activation of 5‐HT 1A receptors in the neurons examined.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, systemic and local administration of 5‐HT 1A receptor agonist 8‐OH‐DPAT inhibited the firing rate of all the PV‐positive neurons examined in the MS‐DB of sham‐operated rats during hippocampal theta rhythm, and these effects were reversed by the selective 5‐HT 1A receptor antagonist WAY‐100635, indicating that these are 5‐HT 1A receptor‐mediated effects. The present results are supported by the fact that the in vitro recordings of septal neurons in brain slices have revealed that activation of 5‐HT 1A receptors hyperpolarizes the neurons and reduces GABA release from GABAergic neurons (Van den Hooff and Galvan, ; Fink and Gothert, ), and consistent with the well‐established role of 5‐HT 1A receptors in the control of neuronal firing of other brain areas. Therefore, the decreased firing rate of PV‐positive neurons in the MS‐DB induced by systemic administration of 8‐OH‐DPAT most likely reflects the direct activation of 5‐HT 1A receptors in the neurons examined.…”
Section: Discussionsupporting
confidence: 88%
“…It was shown previously that LS 5-HT 1A receptors were located primarily on calbindin-positive neurons, indicative for septal GABAergic interneurons ( Aznar et al , 2003 ; Lüttgen et al , 2005 ). Moreover, electrophysiological experiments have established that septal 5-HT 1A receptor activation causes neuronal hyperpolarization ( Joëls et al , 1987 ; Van den Hooff and Galvan, 1992 ). Thus, it is conceivable that a reduced 5-HT function in the LS either during psychological stress exposure ( Kirby et al , 1995 ; Ebner et al , 2008 ) or after 5-HT 1A receptor blockade is associated with an enhanced intraseptal inhibitory function (presumably via GABAergic interneurons).…”
Section: Discussionmentioning
confidence: 99%
“…5-HT1A receptor agonists are one sort of the ligands which is able to activate the 5-HT1A receptors. According to different intrinsic activities, 5-HT1A agonists are clarified in two categories, namely full agonists such as 8-OH-DPAT, F-11440 and flesinoxan, as well as partial agonists such as ipsapirone, gepirone, buspirone and tandospirone [ 17 – 20 ]. Tandospirone is highly potent among partial agonists of 5-HT1A receptor and has a K i value of 27 ± 5 nM.…”
Section: 5-ht1a Receptor and Its Agonistsmentioning
confidence: 99%